A systematic review of involvement and practice of community pharmacy professionals in child health services - Sinha, Rashmi; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
Community Pharmacists (CPs) play a crucial role in delivering Child Health Services (CHS); the extent of their participation, practices, and the challenges and facilitators to providing these amenities remain largely unexamined. This study aims to consolidate existing research regarding the involvement and role of CPs in maternal and CHS. Seven online databases were queried for articles published in English from the records' creation. Studies were selected based on the evaluation of the participation and procedures of CPs in mothers and CHS. All full papers selected for the final analysis were assessed for quality utilizing the Mixed Method Assessment Tool (MMAT), with data extraction performed and verified. A total of 2900 articles were identified. After evaluating the inclusion standards, 14 full-text papers were selected for the final study. Eight research investigations indicated that CPs participated in maternal wellness programs by offering breastfeeding direction, counseling on the advantages of vitamins throughout pregnancy, providing immediate contraception suggestions, and addressing signs of disease such as backache. Three research investigations examined CPs offering guidance on managing acute diarrhea in children. Three investigations additionally provided information on prescription drug counseling and medications for children. CPs identified the perceived opinions of customers, issues with health insurance, time constraints, and inadequate rewards for treatments rendered as the primary obstacles to service delivery. CPs participated in many maternal and CHS within CP environments. The implementation of practices did not align with the combined Federation of International Pharmacy (FIP)/World Health Organization (WHO) recommendations on optimal pharmacy procedures for certain services, including managing symptoms of diarrhea.